2022
DOI: 10.1001/jamanetworkopen.2022.4822
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Mortality Disparities Among American Indian and Alaska Native, Black, and White Patients With COVID-19

Abstract: Key Points Question Are the higher in-hospital mortality rates for COVID-19 among American Indian and Alaska Native patients compared with other racial groups associated with differences in comorbidity burden? Findings In this cross-sectional study of 18 731 US adults hospitalized with COVID-19 in 2020, American Indian and Alaska Native patients had a lower mean comorbidity risk score compared with the overall patient population, yet they were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Another study also evaluated the impact of race on COVID-19 and observed a higher burden of the pandemic on Black and Hispanic individuals, with enhanced mortality, infection rate, and hospitalization [ 49 ]. Other studies tried to evaluate the impact of COVID-19 on the Indigenous peoples, in which enhanced death was observed in American Indians, Alaska Natives, and Indigenous individuals from Australia [ 50 , 51 ]. Finally, only a few studies evaluated individuals with multiracial backgrounds, and higher mortality and admission to ICU has observed [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study also evaluated the impact of race on COVID-19 and observed a higher burden of the pandemic on Black and Hispanic individuals, with enhanced mortality, infection rate, and hospitalization [ 49 ]. Other studies tried to evaluate the impact of COVID-19 on the Indigenous peoples, in which enhanced death was observed in American Indians, Alaska Natives, and Indigenous individuals from Australia [ 50 , 51 ]. Finally, only a few studies evaluated individuals with multiracial backgrounds, and higher mortality and admission to ICU has observed [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the two levels where participants had the most barriers to discuss. The barriers discussed broadly centered on three interrelated issues that acted in synergy to affect the delivery of services: (1) limited health insurance policy, (2) severely inadequate human resources, and [58] (3) limited health infrastructure tailored to CLWCP. All participants were frustrated with Ghana's health insurance policies and inadequacies of the health systems infrastructures like patient assessment rooms, health information systems, and pharmaceutical products for CP care.…”
Section: Structural Barriersmentioning
confidence: 99%
“…Contributing factors that have been posited include a self-perpetuating system of income inequality, disproportionate burden of underlying comorbidities, population dense neighborhoods, family dense households, greater likelihood to work in public-facing occupations, less ability to stop working or to accept a furlough from work, and fewer healthcare resources in the neighborhoods of these communities. 8 , 9 , 10 , 11 , 12 , 13…”
Section: Introductionmentioning
confidence: 99%